Planning for metapopulation persistence using a multiple-component, cross-scale model of connectivity. (March 2016) - Foster, E.; Love, J.; Rader, R.; Reid, N.; Dillon, M.; Drielsma, M.J.
Abstract: Reducing fragmentation and habitat loss by restoring or maintaining connectivity has been promoted as a way to mitigate the negative impacts of human activities on biodiversity. This study is an example of collaboration between spatial researchers and on-ground practitioners, to deliver better informed management options for investment in connectivity and biodiversity outcomes. Using the Border Rivers-Gwydir catchment revegetation programmes in New South Wales, Australia, we describe a fit-for-purpose, cross-scale methodology consisting of multiple-component models, where each component reflected varying spatial scales. The methodology was based on the concepts of metapopulation ecology and landscape ecology and used least-cost paths analyses. At the wider scale, native vegetation extent and condition were used as a surrogate for all biodiversity; at the finer scale, landscape structure and generalised movement parameters related to a focal woodland species group were used to derive least-cost paths. The output from the analyses provided spatially explicit management action zones that were used to prioritise areas for revegetation investment. Combining local priority zones for linking habitat with regional-scale and broad-scale zones should increase access to resources for biota, increase dispersal potential and thereby enhance biodiversity persistence. Promoting connectivity is a global concern. Our approach could be relevant in other geographical settings where the implementation needs of NRM practitioners can be assisted through the application of scientific knowledge. Highlights: A new, multi-scale model for connectivity-focused conservation actions. Integrates habitat structure, quality and species movements across multiple scales. We identify spatially explicit management zones for greater biodiversity outcomes. The model informs decision making for any revegetation programme.